The laboratory rat - Sharp, Patrick E. (The Laboratory animal pocket reference series, 1998)
This guide was created especially for individuals performing research with rats whose duties include animal facility management, animal husbandry, regulatory compliance, and technical procedures involved with their research. Basic information and common procedures are presented in detail.